Design and Construction of a Website-Based Online Sales Information System for Cake Products (Case Study: Vavivegga Business House, Halong) - Haullussy, Vanda Novelish; Pieter Leunupun; Tomasila, Golda (Jurnal Multidisiplin Madani, 2023)
Sales via the internet network can easily make trade connections without any access time limitations and can increase the number or turnover of sales, and can increase the area of marketing locations or product sales accurately. The aim of this research is to design an online sales information system for the Vavivegga business house in order to expand the business that has been created for a long time and to help make the business known to all in the community. Making web applications refers to the RAD Method. The results obtained from the design and development of a website-based online sales information system at the Vavivegga business house can help consumers see the cake products that are made without having to come to the business location, besides making it easier for consumers who want to place orders